Analisis Beban Kerja dan Konflik terhadap Kepuasan Kerja Karyawan - Azis Mauraksa; R.Deni Muhammad Danial; Nor Norisanti (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to determine the effect of employee workload and conflict on job satisfaction. The method used in this study uses an associative method. Data collection techniques used by researchers in research is through observation, interviews, questionnaires, documentation and library research. Data analysis techniques used are multiple correlation techniques, the coefficient of determination and multiple linear regression analysis. Based on the calculation of categorizing the percentage of data scores it is known that the workload is in high criteria. This shows the workload on Sukabumi's Neptuns Screen Printing Convection. Based on the calculation of categorizing data, it is found that the value of the conflict criteria is. This means that conflicts that occur within the company Neptuns Screen Printing Studio can still be resolved. Conclusion, there is a significant influence between workload and conflict on employee job satisfaction Keywords: Workload, Conflict, Job Satisfaction